Are We On Track? AI-Assisted Active and Passive Goal Reflection During Meetings - Chen, Xinyue; Tankelevitch, Lev; Vanukuru, Rishi; Scott, Ava Elizabeth; Panda, Payod; Rintel, Sean (CHI 2025, 2025)
Meetings often suffer from a lack of intentionality, such as unclear goals and straying off-topic. Identifying goals and maintaining their clarity throughout a meeting is challenging, as discussions and uncertainties evolve. Yet meeting technologies predominantly fail to support meeting intentionality. AI-assisted reflection is a promising approach. To explore this, we conducted a technology probe study with 15 knowledge workers, integrating their real meeting data into two AI-assisted reflection probes: a passive and active design. Participants identified goal clarification as a foundational aspect of reflection. Goal clarity enabled people to assess when their meetings were off-track and reprioritize accordingly. Passive AI intervention helped participants maintain focus through non-intrusive feedback, while active AI intervention, though effective at triggering immediate reflection and action, risked disrupting the conversation flow. We identify three key design dimensions for AI-assisted reflection systems, and provide insights into design trade-offs, emphasizing the need to adapt intervention intensity and timing, balance democratic input with efficiency, and offer user control to foster intentional, goal-oriented behavior during meetings and beyond. KEYWORDS: videoconferencing, meeting, goal, intentionality, generative AI, probe, active, passive, intervention, interruption RELATED RESEARCH Formative studies Mental Models of Meeting Goals: Supporting Intentionality in Meeting Technology Prototype studies Before meetings: What Does Success Look Like? Catalyzing Meeting Intentionality with AI-Assisted Prospective Reflection Before and during meetings: The CoExplorer Technology Probe: A Generative AI-Powered Adaptive Interface to Support Intentionality in Planning and Running Video Meetings During meetings: Are We On Track? AI-Assisted Active and Passive Goal Reflection During Meetings - Microsoft Research Between meetings: Designing Interfaces that Support Temporal Work Across Meetings with Generative AI